SAT0166 Dose Adjustment of Biological Treatment in Patients with Rheumatoid Arthritis and Psoriatic Arthritis. Economic Impact Evaluation. (9th June 2015) - Gomez Germá, P.; Rodriguez Valls, M.J.; Aranda-Valera, I.C.; Toledo Coello, M.D.; Cabello Fernandez, Y.; Perez Venegas, J.J.
Abstract : Background: Biological therapies (BT) allowed a better control of disease activity in patients with Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PsA); however, its high cost may be a limitation to widespread use. It seems reasonable to implement a dose adjustment strategy in selected patients that achieve and maintain remission or low activity. Objectives: 1. To analyze the dose adjustment (DA) strategies used with different BT and the clinical outcome assessed by DAS28 in RA and PsA patients in biological treatment followed by second level Hospital Rheumatology Unit. 2. Determine the associated economic impact. Methods: An observational, longitudinal, retrospective and descriptive study by reviewing medical records (from January 2013-January 2015) of patients with RA and PsA on BT, that achieve and maintain clinical remission (DAS28 <2.6) or minimal clinical activity (DAS28 2.6-3.2) for at least 6 months under DA were reviewed. Demographic data, duration of the disease before the use of BT, time of biologic in adjusted doses, clinical evaluation pre and post-optimization by DAS28 (at 6 month) and therapeutic strategies are discussed. DA strategies were: adalimumab (ADA) 40 mg/ 21 days, etanercept (ETN) 25 mg every week, ETN 50 mg every 10 days or every 15 days, certolizumab pegol (CTZ) 200 mg every 4 weeks, abatacept (ABT) 500 mg every 6 weeks and infliximab (IFN) 3 mg/kg every 10 weeks. Annual costs of each treatment were estimated based on the Spanish public ex-factory prices of each drug (€ 494.61 for 40 mg of ADA, € 227.81 for 50 mg of ETN, € 113.90 for 25 mg of ETN, € 455.99 for 200 mg of CTZ, € 322.10 for 250 mg of ABT IV and € 515.90 for 100 mg of IFN). Statistical analysis was performed using IBM SPSS version 20.0 program. Results: From 279 patients with RA and PsA were on biological treatment, 57 (20.43%) were undergoing therapeutic adjustment. 37 (64.9%) were RA and 20 (35.1%) PsA. 36 (63.2%) were women. Mean age was 54±13 years. The mean duration of disease prior to the beginning of biologic treatment was 7.2±5.7 years. The mean time with BT standard dose was 63.7±31 months; the average time on adjusted doses was 13.3±9.9 months. Doses adjustment strategies were: ADA 40 mg every 21 days (24/42, 1%), ETN 25 mg every week (21/36, 8%), ETN 50 mg every 10 days (3/5, 3%) or every 15 days (5/8, 8%), CTZ 200 mg every 4 weeks (1/1, 8%), ABT 500 mg every 6 weeks (1/1, 8%) and INF 3 mg/kg every 10 weeks (2/3, 5%). Before DA, fifty (87.7%) patients were in DAS28 remission and seven (12.3%) in low DAS28 activity. Six months after, 48 (84, 2%) continued to be in clinical remission, 3 (5.3%) in low activity, 4 (7%) in moderate activity and 2 (3.5%) in high DAS28 activity. Six patients (10.5%) needed start over the standard dose of the drug. Table shows the estimated cost per patient and year of each drug and dose pattern. Economic impact and associated savings are also showed. Conclusions: A high percentage of RA or PsA patients in sustained remission or low disease activity after standard biological treatment remain clinically controlled after dose adjustment. The most common DA strategies used were ETN 25 mg weekly and ADA 40 mg every 21 days. This DA strategy entails an estimated savings of over 283, 000€, allowing to treat 27 extra patients without increasing our total budget. Disclosure of Interest: None declared